Spatial Pattern of Living Woody and Coarse Woody Debris in Warm-Temperate Broad-Leaved Secondary Forest in North China - Fang Ma; Shunzhong Wang; Weiguo Sang; Keming Ma (Plants, 2024)
The investigation into the spatial distribution of living woody (LWD) and coarse woody debris (CWD) within forests represents a fundamental methodology for probing the inherent mechanisms governing coexistence and mortality within forest ecosystems. Here, a complete spatial randomness (CSR) null model was employed to scrutinize the spatial pattern, while canonical correspondence analysis (CCA) and the Torus-translation test (TTT) were utilized to elucidate the distribution patterns of LWD and CWD within warm-temperate deciduous broadleaf secondary forests in Dongling Mountains plot, northern China. The results reveal that both LWD and CWD exhibit an aggregated distribution as the predominant pattern in the Dongling Mountains plot, with the proportion and intensity of aggregation diminishing as spatial scale increases. Specifically, the aggregation intensity g0–10 demonstrates a significant negative correlation with abundance and maximum diameter at breast height (DBH). Notably, the g0–10 of LWD manifests a stronger correlation with the maximum DBH, whereas the g0–10 of CWD exhibits a greater association with the mortality rate. CCA outcomes suggest that elevation, convexity, and aspect significantly impact LWD distribution, whereas CWD distribution shows substantial negative correlations with elevation, convexity, slope, and aspect. TTT findings indicate that ecosystems characterized by a substantial presence of LWD also display a notable prevalence of CWD. Additionally, the majority of species exhibit no habitat preference, displaying neutral habitat connections and low ecological niche differentiation within the sampled plot.